XXVIII Italian Melanoma Intergroup National Congress - Florence, Italy | 30 September-2 October 2022 - Italian Melanoma Intergroup (IMI) (PAGEPress Publications, 2023)
Abstracts from the Italian Melanoma Intergroup (IMI) National Congress